When Shari'a Becomes a Science of Law - Sewilam, Heba (AUC Knowledge Fountain, 2021)
The Sharīʿa codification, privatization and reconciliation present three reform movements to scientize Sharīʿa in the manner of liberal positivism. The scientism of Sharīʿa makes Islamic law predictable, rational and objective. Its final goal is to protect Sharīʿa from the political encroachments of the ruling elites and facilitate Sharīʿa implementation in a post-colonial era. The three reform movements are, however, incapable of harmonizing Sharīʿa with the liberal norms of a scientized law. Sharīʿa codification makes the law predictable but neglects Sharīʿa’s undemocratic methods of decision-making. Sharīʿa-compliant legislation is still the monopoly of the Muslim jurists and the ruling caliph. Sharīʿa privatization secularizes Sharīʿa-based arguments in the public sphere, but in the meantime, creates a politics of mistrust due to the suspicion of an Islamist hidden agenda. Sharīʿa reconciliation endeavors to unite Sharīʿa with universal human rights through a Muʿtazilī search for objective values. Yet, doubts in the ever existence of objectivity is likely to abort Sharīʿa’s reconciliation attempts. In all this, the scientism of Sharīʿa is not arriving at its target of reconciling Sharīʿa with liberal laws and purposes but rather eliminating its competitive edge to a hegemonic liberalism.